Reducing periprocedural complications in transcatheter aortic valve replacement: review of paravalvular leaks, stroke and vascular complications. (2nd November 2015) - Paradis, Jean-Michel; Altisent, Omar Abdul-Jawad; RodÉs-Cabau, Josep
Abstract : Transcatheter aortic valve replacement has been established as the standard of care for inoperable patients and a valid alternative for high-risk individuals with severe symptomatic native aortic stenosis. Over the last decade, substantial improvement has been made in the transcatheter technology. Nevertheless, this less-invasive procedure is still associated with complications like paravalvular leaks, strokes and vascular complications. This review article discusses these worrisome complications associated with transcatheter aortic valve replacement and proposes methods to prevent these hurdles.